Historia y memoria del trabajo forzado del sistema concentracionario franquista - Juan Carlos García-Funes; Fernando Mendiola Gonzalo (Cahiers de Civilisation Espagnole Contemporaine)
Captivity and forced labour played a key role in the construction of the New State after the military coup in July 1936. In spite of this importance, there is still an important lack of knowledge about its roots, logics and development when giving an overall picture about Franco’s dictatorship. Regardless the recent efforts carried out by historians and memorial associations, this lack of knowledge reaches the victims’ families and a great part of Spanish society. In this article we deal with the history and memory of forced labour within concentration camps system, the biggest captivity labour system in modern Spain. We aim to stress the importance of this system within Spanish contemporary historiography, taking into account different approaches from researches, social movements and public policies.